2011
DOI: 10.1371/journal.ppat.1002046
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Plasmodium Sporozoites into Liver Stage-Like Forms Is Regulated by the RNA Binding Protein Pumilio

Abstract: Many eukaryotic developmental and cell fate decisions that are effected post-transcriptionally involve RNA binding proteins as regulators of translation of key mRNAs. In malaria parasites (Plasmodium spp.), the development of round, non-motile and replicating exo-erythrocytic liver stage forms from slender, motile and cell-cycle arrested sporozoites is believed to depend on environmental changes experienced during the transmission of the parasite from the mosquito vector to the vertebrate host. Here we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
140
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(143 citation statements)
references
References 58 publications
2
140
1
Order By: Relevance
“…These untranslated mRNAs are stored for translation after fertilization. RNA-binding proteins (Puf proteins) that repress translation by binding to the mRNA 3= untranslated region are specifically upregulated in gametocytes (Puf1 and Puf2) (27,28) and sporozoites (Puf2) (46,47). The phosphorylation of eIF2␣ in salivary gland sporozoites, mature schizonts, and gametocytes induces translational repression and storage of untranslated mRNAs as stress granules (42,52).…”
Section: Translational Control In Plasmodium Sexual Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…These untranslated mRNAs are stored for translation after fertilization. RNA-binding proteins (Puf proteins) that repress translation by binding to the mRNA 3= untranslated region are specifically upregulated in gametocytes (Puf1 and Puf2) (27,28) and sporozoites (Puf2) (46,47). The phosphorylation of eIF2␣ in salivary gland sporozoites, mature schizonts, and gametocytes induces translational repression and storage of untranslated mRNAs as stress granules (42,52).…”
Section: Translational Control In Plasmodium Sexual Stagesmentioning
confidence: 99%
“…It has been suggested that the phosphatase in the salivary glands may be repressed by the RNA-binding protein Puf-2. Indeed, when Puf2 is knocked out in P. berghei, the sporozoites start transforming into liver stages while inside the mosquito salivary glands (46,47).…”
Section: Translational Regulation Of Plasmodium Sporozoitesmentioning
confidence: 99%
“…Meanwhile, Puf6p is involved in translational repression and localization of the ASH1 mRNA (12). Pumilio domain proteins in malaria parasites effect stage-specific translational repression (13,14). In contrast, some pumilio proteins have also been shown to increase expression: for example, in Caenorhabditis elegans olfactory sensory neurons, Fas-binding factor 1 (FBF-1) promotes translation of egl-4 mRNA by binding to its 3=-UTR (15).…”
mentioning
confidence: 99%
“…Intriguingly, in one study, Puf2 knockout in P. berghei altered the gametocyte sex ratio, as observed in P. falciparum (Muller et al, 2011), whereas sex ratio was unchanged with Puf2 knockout in either P. berghei (GomesSantos et al, 2011) or P. yoelii (Lindner et al, 2013). The functions of Puf2 during sporozoite development appear to be conserved in these two rodent parasite species (Gomes-Santos et al, 2011;Lindner et al, 2013). Puf2 deletion in both rodent parasite species resulted in the loss of infectivity and in premature transformation of sporozoites to exoerythrocytic forms, though such changes occurred much earlier during sporogony in P. berghei than in P. yoelii.…”
Section: Discussionmentioning
confidence: 91%
“…Disruption of PfPuf2 results in increased gametocyte differentiation and elevation of the male-to-female sex ratio (Miao et al, 2013). Studies on the Puf2 protein in P. berghei and P. yoelii have shown that knockout of Puf2 results in failure of maintenance of sporozoites in mosquito salivary glands and premature transformation of sporozoites into liver-stage-like parasites (Gomes-Santos et al, 2011;Lindner et al, 2013;Muller et al, 2011). However, Puf1 knockout in P. berghei did not reveal any noticeable phenotypic changes during parasite development (Gomes-Santos et al, 2011;Muller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%